PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBANTU MEDIA POSTER PINTAR MATERI BAGAIMANA BENTUK INDONESIAKU KELAS V - Santi Kasari, Dewi; Nuranisa; Pratiwi, Etty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a valid and practical Student Worksheet (LKPD) using smart posters for the topic "What is My Indonesia" for fifth-grade elementary school students. This research was motivated by the learning process, which was still dominated by lectures and textbooks, resulting in students being less active, easily bored, and less interested in participating. Therefore, innovative and engaging teaching materials were needed to increase student motivation. The research method used was Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The subjects were fifth-grade students of SD Negeri 1 Banyuasin 1. Data collection techniques included interviews, questionnaires, and documentation. Product validation was conducted by media experts, material experts, and language experts. Product trials were conducted through one-on-one and small group sessions to determine the practicality of the developed product. The results showed that the LKPD using smart posters was categorized as very valid with a score of 92,89% and very practicalwith a score of 95,57% for use in learning. This media is able to help students understand the material in a more concrete, interesting and interactive way so that it can increase students' learning motivation in science learning.